ANALISIS MATERI BUKU AJAR BAHASA ARAB SEKOLAH MENENGAH PERTAMA TERPADU RABBI RADIYYAH REJANG LEBONG - Yusuf Muhtarom; Suharsono Suharsono; Fahmi Syaefudin (Fakultas Tarbiyah Universitas Ibrahimy, 2022)
Books are one of the most widely used teaching materials by students and teachers in the learning process. The composition has also been regulated by the applicable instrument regarding its quality. One of the bodies that manages the feasibility of the quality content (content quality) of textbooks is the BSNP. For this reason, in this article the author will analyze the quality of textbooks used by SMPIT RR students by examining the quality standards (standard quality) of textbooks according to BSNP. This article research uses a qualitative method (library research) and the source of the data taken is the quality of the content of the Arabic language textbook at SMPIT RR 2013 curriculum published by Erlangga. The data analysis technique in this article uses content analysis. The results of the analysis of the quality of the content of the Arabic language textbook at SMPIT RR have a good category and have met the quality of content applied by BSNP (analysis from the data revealed that the content quality of Arabic language textbook at SMPIT RR has a good category and has met the content quality applied by the NESA). But there are some shortcomings that need to be written regarding the explanation of the grammatical elements.